2022
DOI: 10.2196/30900
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Use Patterns and Racial and Ethnic Differences in Real Time Affective States During Social Media Use Among a Clinical Sample of Adolescents With Depression: Prospective Cohort Study

Abstract: Background Increasing youth mental health problems over time correlate with increasing rates of social media use (SMU); however, a proposed contributory relationship remains unproven. To better understand how SMU impacts mental health requires a more nuanced understanding of the relationship between different patterns of SMU and specific individual factors. Studies suggest that more active forms of SMU may offer mental health benefits when compared with more passive forms. Furthermore, the literatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Importantly, the COVID‐19 pandemic has disproportionately impacted low‐income families and racial/ethnic minorities (Millett et al, 2020; Perrigo et al, 2022; Tai et al, 2021). Adolescents of color are at greater risk of developing anxiety symptoms following negative live events (e.g., Lewis et al, 2012) and also display differing affect trajectories following SMU (Nereim et al, 2022). These trends highlight the need for future studies to examine effects of coping and SMU on anxiety in diverse representative samples.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the COVID‐19 pandemic has disproportionately impacted low‐income families and racial/ethnic minorities (Millett et al, 2020; Perrigo et al, 2022; Tai et al, 2021). Adolescents of color are at greater risk of developing anxiety symptoms following negative live events (e.g., Lewis et al, 2012) and also display differing affect trajectories following SMU (Nereim et al, 2022). These trends highlight the need for future studies to examine effects of coping and SMU on anxiety in diverse representative samples.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study of which we are aware to capture, code, and interpret videos of young children using media in in-the-moment, naturalistic contexts during early childhood (Nereim et al, 2022). This study confirmed several findings from studies that used parental reports or lab observations, demonstrating the utility of the EMA method to study media in the moment.…”
Section: Discussionmentioning
confidence: 99%
“…Pew Research Center (2022) noted that Black and Hispanic teens were more likely to report being on YouTube, TikTok, and Instagram “almost constantly” compared to White teens. Also, samples of Black teens reported experiencing daily online discrimination (English et al, 2020) and reported more negative affect after social media use than White or Hispanic teens (Nereim et al, 2022). Therefore, it would be important to test if our findings from this study replicate in a more diverse (e.g., race, ethnicity, gender) sample of teens.…”
Section: Discussionmentioning
confidence: 99%